Dissolving pulps by oxidation of the cellulosic fraction of lignocellulosic waste - Ehman, Nanci Vanesa (2017)
The cellulosic fractions of Eucalyptus sp. sawdust pulp and of sugarcane bagasse pulp, which have been subjected to hydrothermal and alkaline treatments, were purified by oxidative means (oxygen and ozone followed by an alkaline extraction) to obtain dissolving pulp. The properties of the obtained pulps were evaluated and compared with commercial dissolving pulps. Eucalyptus sawdust pulp achieved 70% delignification after oxygen treatment and Kappa number was 5.8. Sugarcane bagasse pulps achieved 83% delignification and kappa number of 8.7. Intrinsic viscosities within the range of dissolving grade pulps specifications were obtained in experiences for eucalyptus sawdust pulp. Higher values than required were obtained for sugarcane bagasse pulp. Retained in 18% alkali were within the range of dissolving grade pulp specifications, being the highest values those in experiences where alkaline extraction was in absence of hydrogen peroxide. Hydrogen peroxide addition in alkaline extraction produced high solubility values in both kinds of pulps.